Prognostic Value of the Ratio of the Sum of the Compound Muscle Action Potentials of Three Healthy, Affected Muscles in Patients with Bell’s Palsy - Dahbour, Said (Jordan Medical Journal, 2018)
Background and Aims: Bell’s palsy is the most common cause of unilateral facial muscle weakness. We aim to find out if a single test of facial nerve conduction performed early in the course of the disease, along with the recording of compound muscle action potential (CMAP) of 3 muscles on the affected side compared to the unaffected side would give a reasonable prognosis at 6 months. Materials and methods: Fifty patients with first-time Bell’s palsy were included in the study, and the degree of involvement was assessed based on the House-Brackmann (HB) Grading System at disease onset, 3 months and 6 months. Results: A good outcome (HB grades I and II) was seen in 28 patients (56%), and a poor/moderate outcome (HB grades III to VI) was seen in 22 patients (44%). Of those who had a ratio of ≥ 25% (26 patients), 19 (73%) had a good outcome, while of thos e with a ratio of < 25% (24 patients), 15 (63%) had a poor/moderate prognosis. Fisher’s exact test showed significant correlation between a CMAP ratio of ≥ 25% and a good outcome (p = 0.022). Age, gender, history of diabetes or treatment with steroids was not correlated with prognosis. Conclusion: A one-time three-muscle CMAP ratio of ≥ 25% was highly consistent with a good prognosis